Outreach Nurses' Perceptions of the Spiritual Needs of Their Homebound Older Clients - Egan, Mary (Journal of religion, disability & health, 2006)
Due to poor health, advancing age and isolation, home-bound seniors are likely to have significant spiritual needs. We explored nurses' perceptions of these needs through a focus group with nurses who provide outreach services to frail older adults, we explored nurses' perceptions of the spiritual needs of their patients. Patients' spiritual needs were seen primarily in terms of spiritual distress. This distress was connected to feelings of anger, guilt and the need for forgiveness, estrangement and abandonment, and fear, and concerns regarding identity, worth and personal legacy. The nurse participants identified a number of ways that they dealt with these needs which they had developed largely through working with homebound seniors. Both lack of training and time constraints were seen as barriers to addressing the spiritual needs of patients.